A core–shell multi-drug platform to improve gastrointestinal tract microbial health using 3D printing. (13th March 2020) - Zhu, Li-Fang; Chen, Xing; Ahmad, Zeeshan; Peng, Yu; Chang, Ming-Wei
Abstract: Improving the proliferation of probiotics (ca. Bifidobacterium ) and inhibiting the growth of pathogenic bacteria (ca. Escherichia coli ) is crucial for human health. This study demonstrates the fabrication of core–shell structure fibers using electrohydrodynamic 3D printing to help improve gastrointestinal tract microbial content. These fibers have various geometries and are capable of encapsulating stachyose into cellulose acetate (shell layer) and loading proteoglycan into polyacrylic resin II (core layer). The impact of membrane geometry on drug release behavior and the effect of exchanging the loading site on physicochemical properties of the resulting fibers were studied. The printed fibrous membranes possess a biphasic drug release profile in simulated intestinal fluid with a burst release within the first 12 h and a slower sustained release up to 72 h. The speed order priority for drug release rate of the printed membrane was whole-circle > semi-circle > square. Moreover, the membranes exhibit good biocompatibility on L929 cells and excellent improvement effects on Bifidobacterium bifidum, combining inhibition effects on Escherichia coli . In summary, the dual-drug fibrous membranes presented here and their precision-fabricated patterns pave a new direction for improving the gastrointestinal tract microbial ecosystem health in the human body.